2011
DOI: 10.1537/ase.091215
|View full text |Cite
|
Sign up to set email alerts
|

Mortality profiles of late Pleistocene deer remains of Okinawa Island: evidence from the Hananda-Gama cave and Yamashita-cho cave I sites

Abstract: In the present study, we estimated age at death of extinct deer (Cervus astylodon) excavated from two Late Pleistocene sites in Okinawa Island (the Hananda-Gama Cave and Yamashita-cho Cave I sites) from degree of molar wear. This was done using a regression equation of extant sika deer of known age, and deriving an age estimation equation based on M 3 crown height applicable to fossil specimens. We then reconstructed mortality profiles using 45 and 88 individuals of the Hananda-Gama and Yamashita-cho assemblag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…However, even if this were the case, misestimation would not influence the height of the histograms but would only compress adult size classes. The second peak would still lie at ~70% of estimated longevity, comparable to what Kubo et al (2011) observed in a sample of the Late Pleistocene Ryukyu deer Cervus astylodon, in which the large number of individuals with very worn third molars skewed the histogram toward older age. A juvenile peak could not be recognized for this taxon because only fully erupted third molars were taken into account in this study (m3 does not erupt until two years of age).…”
Section: Adult Mortality and Longevitysupporting
confidence: 79%
See 3 more Smart Citations
“…However, even if this were the case, misestimation would not influence the height of the histograms but would only compress adult size classes. The second peak would still lie at ~70% of estimated longevity, comparable to what Kubo et al (2011) observed in a sample of the Late Pleistocene Ryukyu deer Cervus astylodon, in which the large number of individuals with very worn third molars skewed the histogram toward older age. A juvenile peak could not be recognized for this taxon because only fully erupted third molars were taken into account in this study (m3 does not erupt until two years of age).…”
Section: Adult Mortality and Longevitysupporting
confidence: 79%
“…This is also evident from comparison with examples of definitely catastrophic profiles in the paleontological literature, such as those derived for the prongbuck Cosoryx (= Merycodus) furcatus and the horse Protohippus perditus from Late Miocene deposits in Nebraska (Voorhies, 1969), as well as those for the early ovibovine Plesiaddax depereti, the spiral-horned antelope Urmiatherium intermedium, and the gazelle Gazella dorcadoides from Late Miocene deposits in northern China (Kurtén, 1953). A relevant cervid example of an attritional profile is that presented by Kubo et al (2011) for the deer Cervus nippon from Kinkazan Island, Honshu ( fig. 8B) and Cervus astylodon from Late Pleistocene deposits on the Ryukyu Islands (Kubo et al, 2011: fig.…”
Section: Type Of Profilementioning
confidence: 62%
See 2 more Smart Citations
“…Klein et al (1981) found similarly strong relationships for ordinary least squares regressions with and without log transformation of the predictor variable (crown height), but they argued that this similarity was because most of the teeth in their sample were medium-worn, the stage when a more linear wear rate is expected. Using the same methods as Klein and colleagues, Kubo et al (2011) also found very similar results for raw and log transformed crown heights. PikeTay et al (2000) obtained very similar values for the coefficient of determination for linear and quadratic regressions when examining relationships between various measures of crown height and age, but when there was a difference, the values for the quadratic regressions were higher.…”
Section: Introductionsupporting
confidence: 59%